Polylactide and hybrid silicasol nanoparticle‐based composites. Issue 17 (13th January 2015) - Zhiltsov, Andrey; Gritsenko, Oleg; Kazakova, Valentina; Gorbatsevitch, Olga; Bessonova, Natalia; Askadskii, Andrey; Serenko, Olga; Muzafarov, Aziz
ABSTRACT The effects of the chemical nature and size of the hybrid nanoparticle external layer on the structures and properties of polylactide composites are investigated. Polylactide is used as the matrix polymer, and molecular silicasol particles with γ‐hydroxypropylic, (methoxyacetyl)oxy, and acetoxy surface groups serve as fillers. A preliminary assessment of the thermodynamic compatibility of polylactide with the surface groups of molecular silicasols is performed. The hydrophilic shells of the silicasols prevent their aggregation in the bulk of the nanocomposite. It shows variations in the chemical structure of the surface layer of the nanoparticles as well as their sizes and concentration make it possible to conduct a controlled change of the characteristics of the composites, particularly to eliminate one of the drawbacks of PLA, the low speed of its crystallization. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41894.